Samuel J. Foote at the banks of the Grand River (1928)
1 photograph : sepia toned 4 x 6 cm Samuel J. Foote at the banks of the Grand River. Cataloguer's title. Samuel J. Foote (1873-1936) was born in Grand Bank in 1873. Foote was called to the Newfoundland Bar in 1899 and went to practice with Sir James Winter. Foote entered into politics in 1904. Foote died on December 8, 1936. Good An album containing 323 black and white photographs and 25 pages of text, covering the years 1914 to 1937 of the FOMOWA Fishing Club on the Grand Codroy River on the west coast of Newfoundland. The album's images have been digitized as separate items.